Web-Based Simulation Modules as Supplement for Enhancing Learning in Lecture and Laboratory-Based Engineering Courses - Chaturvedi, S. K.; Prabhakaran, R. (Journal of Engineering Education Transformations, 2015)
Results are presented from an NSF supported project that validate the hypothesis that students` learning gains can be enhanced through integration of web-based interactive simulation and visualization modules in engineering courses. The implemented modules were used in the "supplementation" mode wherein students used these modules along with conventional lecture or laboratory classes. In order to gage the effectiveness of each implemented module a "control" group, without access to the module, and an "experimental" group, with access to the module, were identified. Performance of students in both groups in an identical quiz was analyzed statistically to determine if the introduction of web-based modules favorably affected students learning outcomes. Since both "control" and "experimental" groups may have different demographic profiles-different age, ethnicity, gender etc.-a demographic factor analysis was also conducted for each module to assess if the impact of demographic factors rises to the level of statistical significance. Results of statistical analysis indicated that of the twenty eight learning outcomes tested in eight engineering courses, fifteen showed statistically significant improvement in quiz scores for "experimental" groups over corresponding "control" groups. Even though for thirteen outcomes the quiz scores were generally higher for the "experimental" groups, improvement in quiz scores over the control group performance was not statistically significant. The demographic factor analysis also showed that whereas gender, ethnicity, course load and math SAT scores are not significant factors for the pedagogy of learning with the web-based simulation and visualization modules, the cumulative GPA was a significant factor in five out of nine modules. The results presented in this large scale study, spanning over three engineering disciplines, demonstrates the favorable impact of web-based simulation and visualization modules on student learning. The project has not only led to enhanced student learning in engineering courses and faculty development but it has also contributed to engineering pedagogy by demonstrating the effectiveness of web based simulation and visualization modules when used in the "supplementation" mode with conventional lectures or lab classes.